Pengelompokan Kecamatan di Kabupaten Banyumas Berdasarkan Produktivitas Hasil Tanaman Pangan Menggunakan Metode K-Means Clustering - Retno Dwi Astuti; Puspita, Dian (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2026)
Significant differences in food crop productivity in each sub-district in Banyumas are a major concern that needs to be addressed. This handling is specifically given to sub-districts with low productivity categories. However, the sub-district groups according to their categories are not yet known. Therefore, this study aims to group sub-districts in Banyumas Regency based on food crop productivity. Grouping is done using the K-Means Clustering method. The data used are data on the harvest productivity of five food crop commodities according to sub-districts in Banyumas Regency in 2023. The results obtained that there are five clusters with three clusters having at least one type of food crop that is less productive and two clusters which all types of food crops are productive.